The Exploration of Human Rights from the Perspective of Development Law Theory: What and How? - Suyitno, Didik; Sulaksono, Sulaksono; Sulistyowati, Eny; Disantara, Fradhana Putra (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study analyzes human rights in legal development to ensure that fundamental human rights are not neglected. Human rights are inherent to every human being, derived from religious, moral, and noble cultural values. Everyone is part of society, consisting of individuals with fundamental rights. Human rights-based development planning becomes a benchmark in development planning so that it does not sacrifice human rights but is used as a tool to achieve goals in enforcing the right to development. However, this becomes a challenge that needs to be faced to prioritize human rights without neglecting the public interest. This study aims to develop development strategies based on the close relationship between strategies and development processes with efforts to promote respect for human rights. The study method uses a normative juridical approach. Data were collected through legal literature and legal materials, namely primary, secondary, and tertiary legal materials. The research results show that development law is important to address increasingly complex social changes and ongoing development agendas. The state must prioritize and ensure that business and development align with the fulfillment of the right to a good and healthy living environment rather than opening up space for environmental destruction. The manifestation of the legal development model is to pay attention to the human dimension as the main goal of development, which provides citizens with access to participate in decision-making in various fields of life. The law allocates greater authority to citizens for their self-realization as subjects, not objects shaped and controlled by other subjects.